Factors Associated with Stress Urinary Incontinence During Pregnancy at Pasar Kuok Community Health Center - Maulana, Muhammad Iqbal; Yulia Margaretta Sari (Fakultas Kedokteran Universitas Andalas, 2025)
Objective: This study aimed to analyze the relationship between maternal age, parity, and trimester of pregnancy with stress urinary incontinence (SUI) severity, measured using the International Consultation on Incontinence Questionnaire (ICIQ) score, among 102 pregnant women at Pasar Kuok Health Center. Method: A cross-sectional study was conducted involving pregnant women who completed the ICIQ questionnaire. Data on maternal age, parity, and trimester of pregnancy were collected and analyzed using statistical tests to determine their association with SUI severity. Result: The mean ICIQ scores varied across age groups, parity, and pregnancy trimesters, with the highest scores observed in women aged 31–38 years, multiparous women, and those in the third trimester. However, statistical analysis revealed no significant associations between ICIQ scores and maternal age (p = 0.584), parity (p = 0.945), or trimester of pregnancy (p = 0.136). Conclusion: These findings suggest that maternal age, parity, and trimester of pregnancy may not independently influence SUI severity during pregnancy. Further research is needed to explore other potential contributors to SUI. Early screening and management strategies, including pelvic floor muscle training, remain essential to improving maternal quality of life.